Analysis of Noise and PM2.5 Levels at a Junior High School in Bandung - Clara Angela Brigitha; Didin Agustian Permadi (Fakultas Teknik, 2023)
Junior High School 14 Bandung is a place of learning that is situated on Lapangan Supratman Street and is frequently passed by motorized vehicles that are highly crowded. Public transportation and buses halting at bus stops frequently cause vehicle slowdowns. This state may be subject to noise exposure and a drop in the PM2.5 measure of the ambient air quality. The purpose of this study is to assess PM2.5 levels and noise levels, as well as to examine how the school community perceives its exposure to noise and PM2.5. The field observation method was employed in this study. Measurements of PM2.5 are performed using a pocket PM2.5 sensor, an outside air quality detector, and a sound level meter (indoor). The findings of the noise measurements at 23 of the 24 tested places were louder than the threshold value, which was 55 dBa for the Education Area. The outdoor PM2.5 measurement findings are higher above the 3 g/m3 permitted quality standard. According to the survey's findings, 75% of respondents said noise interferes with learning and teaching, 56% said outdoor PM2.5 had no impact on health, and 99% said interior PM2.5 had no impact on health.